Oxford international english: teacher resource book 1 - Jones, Eileen; Milford, Alison (Oxford University Press Karachi, 2017)
This Teacher Resource Book supports the International English series of student books and workbooks providing you with all the tools to deliver effective language and literacy lessons. It ensures that all skills are taught in consistently throughout your school ensuring pupils core English skills develop quickly.